2013
DOI: 10.4103/0973-029x.110708
|View full text |Cite
|
Sign up to set email alerts
|

Malignant peripheral nerve sheath tumor of facial nerve: Presenting as parotid mass

Abstract: Malignant peripheral nerve sheath tumor (MPNST) is very uncommon tumor of parotid gland and it is an uncommon spindle cell sarcoma accounting for approximately 5% of all soft-tissue sarcoma. There is strong association between MPNSTs and neurofibromatosis (NF-1) and previous irradiation. Structural abnormality of chromosome 17 is associated with NF-1 and so MPNST. We present a case of a 78-year-old male presenting with slowly growing parotid mass who underwent tumor resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…MPNSTs are very rare tumors with incidents of approximately 0.001% in the population [ 3 , 9 ]. These tumors usually affect the proximal extremities and trunk and are very rare in the head and neck [ 6 , 10 – 12 ]. They usually arise in adulthood, with most occurring around 20–50 years of age [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MPNSTs are very rare tumors with incidents of approximately 0.001% in the population [ 3 , 9 ]. These tumors usually affect the proximal extremities and trunk and are very rare in the head and neck [ 6 , 10 – 12 ]. They usually arise in adulthood, with most occurring around 20–50 years of age [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similar to most soft-tissue sarcomas, surgery is the primary modality used to treat MPNSTs of the head and neck, with complete surgical excision of the tumor with negative margins correlating with longer overall survival [ 2 , 6 , 7 , 18 – 21 ]. However, given the relatively small space within the head and neck, the proximity to vital structures, and the potential for microscopic local spread, obtaining negative margins can be difficult.…”
Section: Discussionmentioning
confidence: 99%
“…found that 35% (n=62) of their patients with MPNST had a history of Neurofibromatosis I [20], neither our nor the 9 prior cases of MPSNT arising from the parotid gland have indicated a history of this genetic condition [3][4][5][6][7][8][9][10][11].…”
Section: Accepted Manuscriptmentioning
confidence: 49%
“…Surgical resection usually yields excellent results in the management of these lesions [13,22,24] MPNST arising from the parotid gland have presented as both tender [6,7,[9][10][11] and non-tender [3][4][5]8] masses which have grown slowly over the course of 3-12 months, but can progress in a more accelerated time frame [6]. Of the 9 cases within the literature, only one has shown facial nerve palsy at the time of presentation [6].…”
Section: Accepted Manuscriptmentioning
confidence: 95%
See 1 more Smart Citation